Ageing in Advanced Industrial States Riding the Age Waves - Volume 3 - Tuljapurkar, Shripad; Ogawa, Naohiro; Gauthier, Anne H.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2010)
Population growth slowed across the world in the last decades of the 20th century, changing substantially our view of the future. The 21st century is likely to see the end to world population growth and become the century of population aging, marked by low fertility and ever-increasing life expectancy. These trends have prompted many to predict a gloomy future caused by an unprecedented economic burden of population aging. In response, industrialized nations will need to implement effective social and economic policies and programs. This is the final volume in a series of three. The papers included explore many examples and strengthen the basis for effective economic and social policies by investigating the economic, social, and demographic consequences of the transformations in the structures of population and family. These consequences include changes in economic behavior, both in labor and financial markets, and with regard to saving and consumption, and intergenerational transfers of money and care.
Dynamics of Transitions -- Age-Structural Transitions in Industrialized Countries -- On Age Structures and Mortality -- Long-Run Relationships in Differential U.S. Mortality Forecasts by Race and Sex: Tests for Co-integration -- Fiscal Dynamics and Projections -- Uncertain Demographic Futures and Government Budgets in the US -- Life, Death and the Economy: Mortality Change in an Overlapping-Generations Model -- International Adverse Selection in Life Insurance and Annuities -- Wealth and Health -- Ageing, Family Support Systems, Saving and Wealth: Is Decline on the Horizon for Japan? -- The Future Costs of Health Care in Ageing Societies: Is the Glass Half Full or Half Empty? -- Family and Care -- Family Support for Older People: Determinants and Consequences -- Care of the Elderly and Women$1 (Bs Labour Force Participation in Japan -- Family and Kinship Networks in the Context of Ageing Societies -- Time Use and Labor -- Historical Trends in the Patterns of Time Use of Older Adults -- An Economic Analysis of Age Discrimination: The Impact of Mandatory Retirement and Age Limitations in Hiring on the Utilization of Human Resources in an Ageing Society.s
Keywords: Social sciences; Geriatrics; Population; Demography; Social Sciences; Demography; Geriatrics/Gerontology.; Population Economics